Two new families of tandem repeats isolated from genus Vicia using genomic self-priming PCR - Macas, J; Pozárková, D; Navrátilová, A; Nouzová, M; Neumann, P (Molecular & general genetics, 2000)
A modified genomic self-priming technique was used for rapid isolation of tandem repeats from several Vicia species. Based on homologies of their nucleotide sequences the newly isolated clones were assigned to two repeat families named VicTR-A and VicTR-B. Both families are rich in AT (74%) and are organized as long blocks of tandemly repeated units. The VicTR-A repeats are characterized by a monomer size of 69 bp, whereas the VicTR-B repeat monomer is about 38 bp long, and the two families do not share significant sequence homology. VicTR sequences show different degrees of amplification (up to 10(6)-10(7) copies/haploid genome) in individual Vicia species and are not amplified in other legumes. The abundances of these repeats do not correlate with genome sizes but are similar in species that belong to the same taxonomic section within the genus Vicia. Primed in situ (PRINS) labeling of metaphase chromosomes of V. pannonica revealed that VicTR-A sequences are located predominantly in the telomeric regions of the short arms of all chromosomes. In contrast, labeling of VicTR-B repeats in V. sativa resulted in mainly intercalary bands of various intensities and only weak telomeric signals.
Keywords: Molecular Sequence Data; léčivé rostliny; Sequence Homology, Nucleic Acid; Genome, Plant; hybridizace in situ fluorescenční; polymerázová řetězová reakce; Polymerase Chain Reaction; zastoupení bazí; genom rostlinný; DNA primery; Fabaceae; Plants, Medicinal; In Situ Hybridization, Fluorescence; DNA, Plant; Base Sequence; sekvence nukleotidů; Base Composition; Tandem Repeat Sequences; DNA rostlinná; Species Specificity; sekvenční homologie nukleových kyselin; druhová specificita; molekulární sekvence - údaje; DNA Primers; tandemové repetitivní sekvence